ANALISA KESULITAN SISWA SMA KELAS X DALAM PEMBELAJARAN KIMIA PADA PENDEKATAN CONTEXTUAL TEACHING AND LEARNING BERBASIS TWO TIER MULTIPLE CHOICE INSTRUMENT - Fena Prayunisa; Ermila Mahariyanti (LPPM Institut Pendidikan Nusantara Global, 2022)
The purpose of the study was to analyze the difficulties of senior high school students at class X in learning chemistry using Contextual Teaching And Learning—based Approach on Two Tier Multiple Choice Instruments. This research is a descriptive research. The subjects in this study were students of class X SMAN 1 Masbagik. The samples in this study were determined by purposive random sampling which are the classes that have not reached the KKM, X IPA 2 class consists of 30 students and X IPA 3 32 students. X IPA 2 class will be taught conventionally meanwhile X IPA 3 class will be taught using the CTL approach. The instrument used to measure the students' level of difficulty is a two-tier multiple choice diagnostic test. The two tier multiple choice diagnostic test is a test with 2 tiers where tier 1 contains the answer and tier 2 contains the reason. The highest error percentages of conventional class was 54.1%, 26.8% understand, and 9.6% was misconception. While the CTL had lower error with the perentage 25.55%, 57.% understand, and 7.86% was misconception. It means that CTL affect sudents’ learning achievent about the concept of oxidation-reduction reactions.